2009
DOI: 10.1111/j.1551-2916.2008.02912.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nature of Filler on Densification of Anorthite‐Based Crystallizable Glass+Ceramic System for Low Temperature Cofired Ceramics Application

Abstract: This paper deals with the critical aspects of sintering of crystallizable glass+ceramic system, which is a critical part of low‐temperature‐cofired ceramics (LTCC) process. Densification studies clearly revealed the influence of filler's nature especially at lower glass contents (≤70 vol%) and lower sintering temperatures. In this temperature range, marked improvement in density was observed in the order cordierite>fused silica>mullite>alumina. The decisive role played by wetting of glass on filler has been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…6(d)). This is also supported by Kumar et al [22], who proved that a similar CAS glass with flux (PbO and B 2 O 3 ) content of 5-15 mol% did not wet fused silica even at 1380 • C, but >95% density was still achieved by sintering at 900 • C with 70 vol% glass in their study. Sufficient densification at 900 • C was also observed in the present study.…”
Section: Sintering Mechanismsupporting
confidence: 84%
“…6(d)). This is also supported by Kumar et al [22], who proved that a similar CAS glass with flux (PbO and B 2 O 3 ) content of 5-15 mol% did not wet fused silica even at 1380 • C, but >95% density was still achieved by sintering at 900 • C with 70 vol% glass in their study. Sufficient densification at 900 • C was also observed in the present study.…”
Section: Sintering Mechanismsupporting
confidence: 84%
“…The sintering of commercial or model glass‐ceramic composites was studied by Mohanram et al., Kemethmüller et al., and Eberstein et al . The influence of different ceramic fillers on the sintering behavior of a glass‐ceramic composite was studied by Kumar et al . The sintering and crystallization of glasses for LTCC applications were studied by Panda et al .…”
Section: Introductionmentioning
confidence: 99%
“…A detailed review of the reactions of alumina with glass phases of different compositions was reported by Mu¨ller et al 2 The authors studied the dissolution of alumina, the sintering behavior, and the crystallization of model glassceramic systems. The sintering of commercial or model glassceramic composites was studied by Mohanram et al, 3,4 Kemethmu¨ller et al, 5 and Eberstein et al 6 The influence of different ceramic fillers on the sintering behavior of a glassceramic composite was studied by Kumar et al 7 The sintering and crystallization of glasses for LTCC applications were studied by Panda et al 8 The influence of the glass phases in LTCCs on the densification and microstructure were studied by Eberstein et al 9 The effect of Al 2 O 3 filler quantities on the crystallization of borosilicate glass was studied by Imanaka et al 10 The influence of the particle size of the Al 2 O 3 filler on the densification and dielectric properties of a glass-ceramic composite was studied by Seo et al 11 The microstructural and mechanical properties of glass-ceramic composites were investigated by Zhang et al 12 The influence of the amount of crystallizing product in a glass-ceramic composite on the TCE was reported by Inoue et al 13 The chemical, structural, and mechanical properties of commercial LTCC materials fired using the parameters prescribed by the producer were studied by Jones et al 14 The main physical properties of commercially available LTCCs processed using the parameters specified by the producer are available in datasheets and other open literature. Typically, those materials have a TCE between 3 9 10 À6 and 10 9 10 À6 K À1 , a dielectric constant between 5 and 8 and a flexural strength between 100 and 300 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al [24] has reported that the glass's wetting ability to the fillers is not identical with the order alumina [ silica. Through the liquid phase sintering procedure, alumina-filler had an advantage to be coated by the glass phase comparing with silica-filler.…”
Section: The Effect Of Ceramic Fillers On Glass/ceramic Composite Promentioning
confidence: 99%